IMPLEMENTASI ALGORITMA NAÏVE BAYES DALAM PENENTUAN PEMBERIAN BEASISWA KIP KULIAH (STUDI KASUS STIKI MALANG) - Fitri Nuril Halizah, Cendikia; Kartikasari, Meivi (Jurnal Simantec, 2024)
The Indonesia Smart College Card or often called KIP Kuliah is a government program in the form of educational assistance for high school, vocational or equivalent graduates who come from underprivileged families and have the achievements to be able to continue their studies at tertiary institutions. In order for the scholarship selection process to be right on target, it is necessary to create a system that can recommend participants who are eligible and who are not eligible to receive KIP Kuliah scholarships. This study aims to implement the Naïve Bayes algorithm in determining scholarship awards so that they are right on target. The Naïve Bayes method can help classify data on prospective recipients of KIP Kuliah scholarships. The criteria for determining the classification were obtained through several stages, namely, the results of file selection, online exams and interviews. The dataset used in this study is 100 scholarship recipient data. The accuracy level of implementing the Naïve Bayes algorithm after testing and calculating using the confusion matrix is 98.89%. So based on the results of the calculation suggests that the Naïve Bayes Classifier algorithm can be used to classify the criteria for the award of the KIP College scholarship.Keywords: Scholarship, KIP Kuliah, Classification, Naïve Bayes.